Implementing Net Promoter Score Process in Selected Insurance Companies in Metro Manila - Duyag, Romeo S. Jr.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2013)
In this project study, insurance is defined as the equitable transfer of the risk of a loss in exchange for payment. A company that sells insurance is called insurer while the one who buys is called policy holder. The amount being charged for a certain amount of insurance coverage is called premium. Insurance policy prepares and protects individuals for unexpected future financial loss. One type of insurance is life insurance (LI). Life insurance is a contract between an insured (insurance policy holder) and an insurer or assurer, where the insurer promises to pay a designated beneficiary a sum of money (the "benefits") upon the death of the insured person. LI or life-based contracts tend to fall into two major categories. One is protection policies and the other is investment policies. The former means mostly for lump sum while the latter means commonly for growth of capital by single premium. Insurance parties' relationship includes insured and the policy owner. Insured is the participant in the contract while the policy owner is the guarantor, although, owner and insured can be the same person. On the other hand, the other type of insurance is the non-life insurance (NLI) which includes automobile and homeowners policies or any insurance that is not determined to be LI.
In the Philippines, the Philippine Insurance Commission (PIC) classified a third type of insurance which is the pre-need. It is a plan which serves as contracts, agreements, deeds or plans for the benefit of the plan holders which provide for the performance of future service/s, payment of monetary considerations or delivery of other benefits at the time of actual need or agreed maturity date, as specified therein, in exchange for cash or installment amounts with or without interest or insurance coverage and includes life, pension, education, interment and other plans, instruments, contracts or deeds as may in the future be determined by the Commission.
It was discussed in this study that the marketing strategies used by service companies started in the study of Ziethaml, et. al "Problems and Strategies in Services Marketing" which includes : Reference Listing Unique Characteristics of Services, Unique Services Features and Resulting Marketing Problems, and Suggested Marketing Strategies and Problems Stemming from Unique Service Features.
The project study discussed the Net Promoter Score (NPS) framework and impact in terms of customer retention. It defined the three types of customers involved in NPS which are promoter, passive, and detractors. Promoter is a customer who gives a score of nine or ten when asked how likely he or she will recommend to others a certain product or service. Passive is a customer who gives a score of seven or eight for the same question. Detractor is a customer who gives a score between zero and six. It showed that the computation of NPS is promoters minus detractors in terms of percentage - the bigger the score, the better. As part of the framework, review of related studies and reports described the rationale of NPS through sample scenarios where the three types of customers are recognized. These scenarios are the closing of some local banks in the Philippines, about recommending Philippine tourism, and customer experiences (CE's) of two policy holders.
This study focused on implementing NPS in selected insurance companies in Metro Manila, Philippines and correlated it with financial performance. The methodology describes that the collection of data is through SurveyMonkey (SM), an on-line survey. Links being accessed were sent via email. There were four surveys prepared for this study namely general NPS survey, employee NPS survey (life), employee NPS survey (non-life), and non-life NPS survey to cover different participants.
Results revealed that there were ninety-seven respondents in the general NPS survey, thirty-eight in non-life NPS survey while only seven and five respondents for employee NPS survey (life), employee NPS survey (non-life) respectively. Both life and non-life insurance companies for the employee surveys obtained a very low NPS which translates that most of the employees specific to two companies will not likely to recommend their company's products or the insurance policy. The NPS obtained for employee survey (life) is zero while employee survey (non-life) insurance is -6 percent. The overall NPS for life is -9 percent while for non-life is - 13 percent. Thus, insurance industry is not performing well in terms of customer retention aspect as compared to other industries.
The overall conclusion of this study is that, insurance industry is not performing well in terms of customer retention aspect. The passive employee group in life insurance can be transformed into promoters while detractors employee group in the non-life insurance needs to decrease NPS. NPS survey in the system is helpful to predict the future of the company, however, relying on the social media will just return low response rate as more responses were collected from those who had been contacted by the author via email. Since NPS passive scores (seven and eight) are insignificant in the total scoring, NPS as a system can best be supplemented with a tool that would measure significance of the result. Generally, with the low NPS score obtained int he study, there is so much to improve in the products and services of the concerned companies.
Essentially, the negative NPS for both LI and NLI companies is not a good picture for insurance industry in the Philippines. Hence, it was recommended to consider further studies on marketing strategies (that will impact premiums and retention), on public perception, and on annual NPS for single entry. It was also noted to take into consideration that companies should intensify the information drive on the difference between pre-need companies and insurance companies in terms of products and services, should understand the significance of the non-respondents in terms of perspective, should know the distinction among LI, NLI and pre-need companies, and should shift focus on customer relationship marketing using NPS as a major tool. It was elevated in this study to continue information dissemination especially on the difference between an insurance company and a pre-need company in order for the promoters to win the detractors and passives. Finally, insurance companies may consolidate or merge to strengthen holdings and increase actuarial life.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Insurance companies -- Metro Manila; Net Promoter Score Process